THE EFFECTIVENESS OF POLICY PROHIBITION OF THROWING WASTE INTO THE RIVER IN BABAKANPARI VILLAGE, CIDAHU DISTRICT, SUKABUMI REGENCY - Dina Siti Astuti; Dian Purwanti; M. Rijal Amirulloh (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2022)
In the Peraturan Daerah Kabupaten Sukabumi Nomor 13 Tahun 2016 concerning Waste Management and Retribution for Waste/Hygiene Services Subsection 26 Verse f regarding the prohibition of throwing waste into the river, it turns out that it is still violated by several communities in Babakanpari Village, Cidahu District, Sukabumi Regency. The purpose of this study was to determine the effectiveness of the policy of banning waste into the river in Babakanpari Village, Cidahu District, Sukabumi Regency. To find out the effectiveness of the policy of prohibiting waste disposal in Babakanpari Village, Cidahu District, researcher uses a theory from Richard E. Matland which stated